Kapital Sosial Organisasi Himpunan Mahasiswa Pendidikan Sosiologi (Himadiksio) Kabinet Inspiratif di Era Pandemi Covid-19 - Rizki Setiawan; Ainun Rahayu (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2022)
The Covid-19 pandemic has an impact on the activities of student organizations, this be seen from the various obstacles they face in carrying out organizational activities. This study intends to determine the social capital in the sociology Education Student Association (Himadiksio)Kabinet Inspiratif in carrying out organizational activities in the Covid-19 pandemic. Determination on informans in this study using nonprobability sampling with purposive sampling technique with subject who are students of Sociology Education who are members of the Sociology Education Student Associaton (Himadiksio) Kabinet Inspiratif. The research method used is descriptive qualitative research. Retrieval of data through interviews and documentation. In examining this paper used social capital theory. The sosial capital in the Sosiology Education Student Association (Himadiksio) Kabinet Inspiratif is a believe, social norms and social network. With this social capital in the Sociology Education Student Association (Himadiksio) can survive and carry out various work programs in the Covid-19 pandemic and achieve the organizational goals that have been declared.